SISTEM PENGGAJIAN KARYAWAN PADA LKP GRACE EDUCATION CENTER - Muhammad Dedi Irawan; Laila Hasni ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - Many agencies and companies are required to modernize management management from manual systems to computerized systems. LKP Grace Education Center is an institution that stands in the field of education where its main activity is to serve and provide the best service, and also employs quite a number of employees, the payroll system currently running at LKP Grace Education Center still uses traditional / manual methods. Delays often occur in processing employee salaries due to the accumulation of salary payment processing that is still done traditionally / manually, because data must be recorded or processed repeatedly in an effort to compile employee salary reports. With the existence of a computerized system it is expected to improve work efficiency, speed, and accuracy in a decision making. In an effort to prevent fraud that might occur to payroll to the workforce it is necessary to have a payroll information system, where there are forms, records and procedures used to determine the salary that must be given to the workforce. Keywords - Systems, Payroll, Employees.